LIQUIFACTION AND ITS IMPACT ON THE COMMUNITIES IN JONOOGE VILLAGE AND SOUTH SIBALAYA VILLAGE, SIGI REGENCY - Endang Herdianti; Eko Jokolelono; Nudiatulhuda Mangun (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Natural disasters, in addition to causing physical damage and loss of life, also impact the local economy to a certain extent. Disasters can paralyze the economy by destroying infrastructure, disrupting communication networks, causing disease outbreaks, crop failures, and other causes. The purpose of this study was to determine the income of residents of Jono Oge Village and South Sibalaya Village before and after the natural disaster, to understand the shift in employment opportunities, and to determine the importance of regulations as a mitigation measure going forward. Data analysis shows that the socio-economic conditions of the community in Jono Oge Village and South Sibalaya Village have changed, meaning that before the liquefaction natural disaster, the community's socio-economic conditions were balanced and after the disaster, the community's socio-economic conditions experienced less positive changes. After the disaster, health facilities and services decreased slightly due to the disaster, the education of school-age children was hampered due to the teaching and learning process at school and the condition of community houses that were damaged and lost. The current condition after the rehabilitation phase should be like the construction of elementary schools and community health centers. The economic side after the earthquake was completely paralyzed, because all economic activities had no source of livelihood, resulting in a decrease or even loss of community income, because there was no production process running. For this reason, mitigation regulations are needed to face natural disasters in the form of earthquakes and liquefaction